454. Perinatal Risk Factors Associated with Skin Infection Hospitalisation in Western Australian Aboriginal and Non-Aboriginal Children - Barnes, Rosanne (Open Forum Infect Dis, 2019)
BACKGROUND: Hospitalisation with skin infection in Western Australian (WA) Aboriginal children is common, with the highest rates in infants and children from remote WA. We aimed to quantify infant, maternal, and sociodemographic risk factors for skin infection hospitalization in WA children, focusing on Aboriginal children aged <17 years. METHODS: We conducted a retrospective population-based cohort study with linked perinatal and hospitalization data on WA-born children (1996–2012), of whom 31,348 (6.7%) were Aboriginal. We used Cox regression to calculate adjusted hazard ratios and associated population attributable fractions (PAFs) for perinatal factors attributed to the first hospitalization with skin infection. To identify specific risk factors for early-onset infection, we further restricted the cohort to infants aged <1 year. RESULTS: Overall, 5,439 (17.4%) Aboriginal and 6,750 (1.5%) non-Aboriginal children were hospitalized at least once with a skin infection. Aboriginal infants aged <1 year had the highest skin infection hospitalization rate (63.2/1,000 child-years). The strongest risk factors in Aboriginal children aged <17 years were socio-economic disadvantage, very remote location at birth and multi-parity (≥3 previous pregnancies) accounting for 24%, 23% and 15% of skin infection hospitalizations, respectively. Other risk factors included maternal age <20 years, maternal smoking during pregnancy and low birthweight. CONCLUSION: We have quantified the relative influence of perinatal risk factors associated with skin infection hospitalizations in WA children, providing measures indicating which factors have the potential to reduce the most hospitalizations. Our evidence supports existing calls for substantial government investment in addressing underlying social and environmental barriers to healthy skin in WA Aboriginal children but also identifies potential areas to target health promotion messaging at individuals/families on maternal smoking during pregnancy and skin hygiene for families. DISCLOSURES: All authors: No reported disclosures.